Efficient synthesis of Triazolo[4,5-d]pyrimidine-7-carbonitriles and Imidazole-4,5-dicarbonitriles using Triethylorthoalkylates and their structural characterisation by Single-crystal x-ray diffraction - Al-Azmi, Amal; Mickey Vinodh (Kuwait Journal of Science, 2021)
Abstract Cyclisation of 5-amino-1-(4-nitrophenyl)-1H-1,2,3-triazole-4-carbimidoyl cyanide and 3-amino-3-((Z)-2-cyano-2-phenylvinylamino) maleonitrile using either triethyl orthoformate or triethyl orthopropionate in dimethylformamide (DMF):1,4-dioxane (1:1 v/v) mixture under reflux conditions afforded 5-alkyl-3-(4-nitrophenyl)-3H-[1,2,3]triazolo[4,5-d]pyrimidine-7-carbonitriles and (Z)-1-(2-cyano-2-phenylvinyl)-2-alkyl-1H-imidazole-4,5-dicarbonitriles, respectively, in moderate to good yields. The structures of these novel compounds were confirmed with 1H/13C nuclear resonance (NMR), infrared spectroscopy (IR), and high-resolution mass spectroscopic methods. Two representative compounds from these molecules, namely 5-ethyl-3-(4-nitrophenyl)-3H-[1,2,3]triazolo[4,5-d]pyrimidine-7-carbonitrile and (Z)-1-(2-cyano-2-phenylvinyl)-1H-imidazole-4,5-dicarbonitrile, were further analysed by the single-crystal X-ray diffraction method. A comprehensive study of structural features and intermolecular interactions present among these heterocyclic compounds was carried out. The crystal data were further examined by a Hirshfeld surface analysis, which provided both qualitative and quantitative information on various intermolecular interactions experienced within the crystal network.